2007
DOI: 10.1096/fasebj.21.5.a682-c
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Vitamin A in Bolivian Fortified Cooking Oil

Abstract: Fortification of a commonly consumed food is often an effective and relatively inexpensive method to alleviate the problem of human vitamin A deficiency. However, among the problems associated with food fortification, stability of the nutrient in the food vehicle must be considered. We tested stability of vitamin A (retinyl palmitate) in commercially available fortified cooking oil from Bolivia under parameters of storage time, temperature and humidity, and light exposure, in both opaque and translucent origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The effect of initial quality of the oil on fortification was studied by some workers previously. Viana, Boy, Boutilier, Furr, and Craft () and Andarwulan et al. () found that initial PV of the oil had an important effect on stability of vitamin A during the shelf life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of initial quality of the oil on fortification was studied by some workers previously. Viana, Boy, Boutilier, Furr, and Craft () and Andarwulan et al. () found that initial PV of the oil had an important effect on stability of vitamin A during the shelf life.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of initial quality of the oil on fortification was studied by some workers previously. Viana, Boy, Boutilier, Furr, and Craft (2007) and Andarwulan et al (2014) found that initial PV of the oil had an important effect on stability of vitamin A during the shelf life. Hemery et al (2015) also suggested that oils with a good initial quality should only be used in fortification of cooking oil with vitamins A and D. Since fatty acid composition of the oils (Choe & Min, 2006), PV, secondary oxidative products, acidic value, and antioxidant component are effective factors on oxidation potential of the oil during cooking; the fatty acid composition, oxidative indexes, and antioxidant activity were assessed, and results are shown in Table 1 and 2, respectively.…”
Section: Characteristics Of the Samplesmentioning
confidence: 99%
“…A PV level of <2 meq kg À1 has been proposed as a key parameter at the time of production . Concomitantly, the quality of vegetable oil (assessed by PV) prior to fortification has been shown to have a dramatic effect on the stability of retinyl palmitate (Andarwulan et al, 2014); the same authors have shown that where a vegetable oil is oxidised through elevated levels of peroxides, it will significantly impact the loss of vitamin A (Viana et al, 2007;Pignitter et al, 2014a). Hydroperoxides are very unstable and decompose into a series of aldehydes, ketones, hydrocarbons, alcohols and many more reaction products as the oil oxidation process continues.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation level greatly interacts with the stability of vitamin A added to the oil. Vitamin A oxidizes faster and loses its activity in the presence of highly-oxidized oils (with a high level of peroxide) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%